2018
DOI: 10.21292/2075-1230-2018-96-10-63-69
|View full text |Cite
|
Sign up to set email alerts
|

Use of Hepatoprotectors During Tuberculosis Chemotherapy: Review of the Russian and International Studies

Abstract: Представлен обзор отечественных и зарубежных исследований, посвященных применению на фоне противотуберкулезной терапии гепатопротекторов, в том числе препаратов производных метионина и содержащих янтарную кислоту�

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
2
0
3
Order By: Relevance
“…The incidence of side effects from the liver is 44-60% of cases, which is confirmed by the results of studies by many researchers (Ivаnovа and Borisov 2018;Stаrshinovа et al 2018). It was found that hepatotoxicity is more often associated with taking first-line anti-TB drugs -Rifampicin (67%), Pyrazinamide (30%), and Isoniazid (7%) (Schaaf et al 2016;Stаrshinovа et al 2018). To prevent the development of toxic reactions, at the same time with the start of anti-tuberculosis chemotherapy, it is recommended to prescribe corrective drugs to patients.…”
Section: Anti-tb Drugs For Childrensupporting
confidence: 57%
See 1 more Smart Citation
“…The incidence of side effects from the liver is 44-60% of cases, which is confirmed by the results of studies by many researchers (Ivаnovа and Borisov 2018;Stаrshinovа et al 2018). It was found that hepatotoxicity is more often associated with taking first-line anti-TB drugs -Rifampicin (67%), Pyrazinamide (30%), and Isoniazid (7%) (Schaaf et al 2016;Stаrshinovа et al 2018). To prevent the development of toxic reactions, at the same time with the start of anti-tuberculosis chemotherapy, it is recommended to prescribe corrective drugs to patients.…”
Section: Anti-tb Drugs For Childrensupporting
confidence: 57%
“…According to the literature Borisov 2017, 2018;Schegertsov et al 2018;Athulnadh et al 2020;Laghari et al 2020;van der Walt et al 2020), the most frequent side effects associated with the use of chemotherapy in patients with tuberculosis infection are toxic reactions (hepatotoxicity, gastrotoxicity, nephrotoxicity) and allergic reactions. The incidence of side effects from the liver is 44-60% of cases, which is confirmed by the results of studies by many researchers (Ivаnovа and Borisov 2018;Stаrshinovа et al 2018). It was found that hepatotoxicity is more often associated with taking first-line anti-TB drugs -Rifampicin (67%), Pyrazinamide (30%), and Isoniazid (7%) (Schaaf et al 2016;Stаrshinovа et al 2018).…”
Section: Anti-tb Drugs For Childrenmentioning
confidence: 69%
“…Согласно проведенным исследованиям, причиной возникновения нежелательных явлений является не только непосредственное воздействие лекарственного препарата, но и ряд факторов, таких как возраст, пол, сопутствующие заболевания, индивидуальная чувствительность организма к лекарственному веществу и непосредственное воздействие самого инфекционного агента на гепатоциты [21].…”
Section: резюмеunclassified
“…1. МСКТ пациента М., 61 год, с двусторонней пневмонией, больного COVID-19 том 7 №6 / 2020 Анестезиология и реаниматология / Pain, Critical Care and Anesthesia мальных показателях общего билирубина -20,3 мкмоль/л, щелочная фосфатаза в норме (93 Ед/л), что характеризует гепатоцеллюлярный тип поражения печени [21]. Показатели свертываемости крови без существенных изменений (активированное частичное тромбопластиновое время -27,1 с; международное нормализованное отношение -1,08; протромбин по Квику -3,38 мг на 100 мл плазмы крови; протромбиновое время -14,8), за исключением некоторого снижения протромбинового индекса -86 %.…”
Section: анестезиология и реаниматология / Pain Critical Care and Anunclassified
“…Гепатотоксические реакции (ГТР) у больных туберкулезом, получающих противотуберкулезные препараты (ПТП), отмечаются, по данным разных авторов, в 44-60% случаев и проявляются нарушением дезинтоксикационной, белковосинтетической и других функций печени [6]. Согласно исследованиям, у впервые выявленных больных туберкулезом и у больных, получавших лечение по 1-му режиму химиотерапии, основными виновниками развития ГТР являлись рифампицин (67% случаев), пиразинамид (30%) и изониазид (7%) [3].…”
unclassified